Analysis of Numeracy Ability of Class VII Students SMP Negeri 1 Siantar - Gayus Simarmata (Edunesia: Jurnal Ilmiah Pendidikan, 2023)
Arithmetic is a field of mathematics closely related to human existence. It will be helpful for anyone to perform any task that requires calculation if they have a basic understanding of mathematics. However, sometimes it is optional to carry out precise calculations. Counting is the backbone or breath of learning mathematics. Students' ability to count becomes vital in teaching mathematics to students. The research aimed to measure Class VII students' numeracy skills at SMP Negeri 1 Siantar, Simalungun Regency. The method used is a descriptive-quantitative approach. The population is nine classes with 254 students, and the sample is taken in layers and randomly as many as four classes with 112 students. The nine classes consist of 2 groups, namely the Superior Class (KU) of 2 classes, namely class VII1 and class VII2, and the Ordinary Class (KB) of 7 classes, namely class VII3, VII4, VII5, to class VII9. The research concluded that the Superior Class could count, while the Ordinary Class was 5.95% unable to count. The findings of this study imply that apart from providing students with a better learning environment and infrastructure, it is essential to improve their arithmetic skills.